Peace Education dalam Pendidikan Agama Islam di Indonesia - Yulita, Rosi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Peace education is a concept that is considered good in the world of education. This research examines Peace education in Indonesia because of the diversity that exists in Indonesia. The research method used is library research. In Islam, coaching and education so as not to do something that can harm other parties is well explained in the Qur'an, namely, the command to do amar ma'ruf nahi munkar, apart from that, in Islam also given directions that as their Muslims must have good manners or akhlaqul karimah. This directive is in accordance with the existing pluralists in Indonesia.